Acute Stress Disorder and Forms of Narrative Disruption - Currier, Joseph M. (Pragmatic Case Studies in Psychotherapy, 2010)
Intervening with persons in the immediate aftermath of potentially traumatic events poses a number challenges for clinicians. Particularly in clinics that serve military personnel or other populations whose livelihoods may depend on regaining functioning efficiently following trauma, there is a need for sensitive and effective psychotherapies for acute stress disorder (ASD), a diagnostic category which attempts to capture maladaptive responses to trauma within the initial four weeks. In this context, Palgi and Ben-Ezra (2010) developed "Back to the Future," a novel treatment for ASD guided by narrative and constructivist understandings of posttraumatic adjustment (e.g., Neimeyer, 2009; White & Epston, 1990). One of the distinctive aspects of Palgi and Ben-Ezra's approach involves a departure from exposure-oriented models of psychotherapy so as not to strengthen the substantive core of the traumatic experience for the survivor -- called the "traumatic nucleus" -- in the early adjustment period. My discussion of Palgi and Ben-Ezra's case of Mr. G and related general issues uses a framework of three common forms of narrative disruption after trauma. Specifically, I first discuss "narrative dominance" as a particular strength of the Back to the Future